2020
DOI: 10.1002/jnr.24647
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related hearing loss: Why we need to think about sex as a biological variable

Abstract: It has long been known that age‐related hearing loss (ARHL) is more common, more severe, and with an earlier onset in men compared to women. Even in the absence of confounding factors such as noise exposure, these sexdifferences in susceptibility to ARHL remain. In the last decade, insight into the pleiotrophic nature by which estrogen signaling can impact multiple signaling mechanisms to mediate downstream changes in gene expression and/or elicit rapid changes in cellular function has rapidly gathered pace, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 164 publications
(226 reference statements)
4
46
0
Order By: Relevance
“…Similarly, one study showed the same results [34], and another study after adjusting for age using covariance analysis found signi cant gender differences in pure tone thresholds at 4 kHz and 8 kHz [32]. It is not unclear whether these gender differences can solely be attributed to estrogen; however, in measuring hearing, gender as a biological variable has attracted the attention of researchers [14]. It is worth noting that there is a signi cant correlation between HFHL and CI in females, while similar results can be found merely in males with hypertension (OR: 2.585, 95% Con dence Interval: 1.099-6.082).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, one study showed the same results [34], and another study after adjusting for age using covariance analysis found signi cant gender differences in pure tone thresholds at 4 kHz and 8 kHz [32]. It is not unclear whether these gender differences can solely be attributed to estrogen; however, in measuring hearing, gender as a biological variable has attracted the attention of researchers [14]. It is worth noting that there is a signi cant correlation between HFHL and CI in females, while similar results can be found merely in males with hypertension (OR: 2.585, 95% Con dence Interval: 1.099-6.082).…”
Section: Discussionmentioning
confidence: 82%
“…Exploring the relationship between differentfrequencies HL and CI is helpful to reveal the in uence of ARHL on CI in different stages of the disease and work toward a more targeted early intervention. Moreover, a few studies have revealed gender differences in HL [14,15]; some studies have found that HL is more prevalent in males than females, and that the decline in hearing thresholds at 6 kHz to 12 kHz was signi cantly rapid in females than males [16]. Aging also plays a role; for example, older adults female (> 70 years) demonstrated a faster rate of change at 0.25 kHz to 2 kHz than younger female (60-69 years), and older adults male had a faster rate of change at 6 kHz than younger male [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the evidence of estrogen to protect hearing mainly focuses on ARHL in postmenopausal woman and the effect of hormone therapy on the auditory organ is still unclear. In the current era of translation research and personalized medicine, future basic and clinical investigations to elucidate the sex differences in the cochlea are essential to help to develop personalized therapeutic strategies against ASNHL [ 148 , 150 , 151 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Many clinicians recognize that normative hearing data are crucial for all age groups [13] , [14] and both sexes [15] , and are essential for describing the normal course of clinical conditions in a community and for developing standards of care [16] . Comparing a patient's standard hearing data (e.g., pure-tone air- and bone-conduction thresholds) to a large sample of his/her healthy age-cohort in their community makes it is possible to identify and treat abnormal declines [16] .…”
Section: Introductionmentioning
confidence: 99%